2019
DOI: 10.1051/e3sconf/201911600002
|View full text |Cite
|
Sign up to set email alerts
|

The influence of physical and mechanical properties of additional materials on the recycled rubber structure during its disposal

Abstract: During the rubber long-term storage in the open air and under the influence of certain temperatures, there is a real threat to the environment where environmental damages cannot be ignored. The objective of this paper is to study the mechanical properties of rubber during its processing by vulcanization after adding some materials to improve their properties. The used materials are: rubber from tires where the proportion of rubber varies from 70-78%, vulcanization granules of rubber, non-vulcanized natural NR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This research was conducted in a lab environment using specially designed laboratory machines and on-farm using experimental units [1].In the context of disruption of the link between a grain and an ear, it was found that multiple stress on grain mass disrupts the link between a grain and an ear. Separation of a grain and an ear rises with an increase in impact frequency, but at high speeds [3] there is a reduction [4] in the quality of a grain and excessive grain shattering [5].…”
Section: Introductionmentioning
confidence: 99%
“…This research was conducted in a lab environment using specially designed laboratory machines and on-farm using experimental units [1].In the context of disruption of the link between a grain and an ear, it was found that multiple stress on grain mass disrupts the link between a grain and an ear. Separation of a grain and an ear rises with an increase in impact frequency, but at high speeds [3] there is a reduction [4] in the quality of a grain and excessive grain shattering [5].…”
Section: Introductionmentioning
confidence: 99%